Exogenous niacin treatment increases NADPH oxidase in kiwifruit - Zhu,X. (2018)
Abstract Kiwifruit are a popular fruit worldwide; however, plant growth is threatened by abiotic stresses such as drought and high temperatures. Niacin treatment in plants has been shown to increase NADPH levels, thus enhancing abiotic stresses tolerance. Here, we evaluate the effect of niacin solution spray treatment on NADPH levels in the kiwifruit cultivars Hayward and Xuxiang. We found that spray treatment with niacin solution promoted NADPH and NADP+ levels and decreased both O2·- production and H2O2 contents in leaves during a short period. In fruit, NADPH contents increased during early development, but decreased later. However, no effect on NADP+ levels has been observed throughout fruit development. In summary, this report suggests that niacin may be used to increase NADPH oxidases, thus increasing stress-tolerance in kiwifruit during encounter of short-term stressful conditions.